2016
DOI: 10.1016/j.comnet.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Multicast Algorithms in Opportunistic Mobile Social Networks using Community and Social Features

Abstract: Opportunistic Mobile Social Networks (OMSNs), formed by people moving around carrying mobile devices, enhance spontaneous communication among users that opportunistically encounter each other without additional infrastructure. Multicast is an important communication service in OMSNs. Most of the existing multicast algorithms neglect or adopt static social factors that are inadequate to catch nodes' dynamic contact behavior. In this paper, we introduce dynamic social features and its enhancement to capture node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In this experiment, the value of nodes' buffer size in the network is set to 1,2,3,4,5,10,20,30,40,50,60,70,80,90, and 100 MB, respectively. Figures 13 and 14 illustrate the change of the delivery ratio within a scenario where 2 regions are included, and each region includes 100 and 200 nodes, respectively.…”
Section: The Impact Of Nodes' Buffer Size On Routing Algorithm Performentioning
confidence: 99%
See 2 more Smart Citations
“…In this experiment, the value of nodes' buffer size in the network is set to 1,2,3,4,5,10,20,30,40,50,60,70,80,90, and 100 MB, respectively. Figures 13 and 14 illustrate the change of the delivery ratio within a scenario where 2 regions are included, and each region includes 100 and 200 nodes, respectively.…”
Section: The Impact Of Nodes' Buffer Size On Routing Algorithm Performentioning
confidence: 99%
“…In mobile opportunistic social networks (MOSNs), mobile users move around and conduct message transmission by using portable devices in which the device‐to‐device communication technology is applied . Detailedly, the portable devices carried by users usually have the capacity of wireless communication via Bluetooth or Wi‐Fi and then could conduct message exchange with each other when they are in communication range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So we can use these algorithms to divide nodes into different communities easily. Regarding the second assumption, many existing works [13][14][15][16] have argued this issue, and their conclusions have shown that many human traces follow power law or exponential distribution. In fact, even for the network that intercontact time does not follow a clear distribution, this assumption is still reasonable.…”
Section: Assumptions and Notationsmentioning
confidence: 99%
“…The network performance of opportunistic networks is associated to the social relationships between users; based on this criterion, in [28,46,16], the authors evaluate a utility-based cooperative data dissemination system, and propose a model of message dissemination considering key factors such as the allocation of nodes, the popularity and data utility. The idea of actively involving users with tasks of minimum impact on their regular activities is also employed by crowdbased participatory systems [23,24].…”
Section: Related Effortsmentioning
confidence: 99%